NILAI MORAL DALAM TOKOH CERITA BUAYA LEARISA KAYELI: KAJIAN SASTRA ANAK [Moral Value in Character of Learisa Kayeli's Crocodile Story: A Study of Children's Literature] - DUDUNG ABDULAH (TOTOBUANG, 2021)
This study aims to discover the moral value in character of Learisa Kayeli's Crocodile story written and developed by Asrif. Literary studies talking about children's literature through Maluku folklore are still not found in scientific journals. Therefore, the theory used in this study is the children’s literature theory of Burhan Nurgiyantoro. The research method used descriptive method of content analysis. This study describes the qualifications and disclosure of the character from the story as an introduction in interpreting the moral values. This story was chosen because (1) it has never been examined using children's literature theory; (2) the important characters are played by animal characters and result in more readers’ imagination compared to stories with human characters; (3) this story is intended for children especially for the fourth, fifth, and sixth graders; (4) it has a complete storyline; and (5) it is printed Maluku folklore written in Indonesian and went through digitalization process. This study concludes that there are seven moral values conveyed by the author in character of Learisa Kayeli's Crocodile story, namely: (1) do not be afraid to defend the truth or to quell tyranny even though life is at stake in order to create a harmonious and peaceful life; (2) appreciate the one who has contributed in (saving) your life in order to establish eternal brotherhood until the end of life; (3) do not disturb the peace of other people's lives so that your lives remain fortune; (4) never give up in trying to do something so that your dreams can be achieved; (5) make good friends with others so that you may be accepted by anyone and anywhere including in any new environment; (6) be patient in solving any obstacles in life so you can cherish other people; and (7) be wise to the surrounding environment in order to create a healthy natural balance so that it can provide benefits for mankind. Kajian ini bertujuan menelusuri nilai moral dalam tokoh cerita rakyat Maluku berjudul Buaya Learisa Kayeli yang ditulis dan dikembangkan oleh Asrif. Kajian sastra yang mengangkat tentang sastra anak melalui cerita rakyat Maluku masih belum ditemukan dalam karya ilmiah. Teori yang digunakan dalam kajian ini adalah teori sastra anak. Metode penelitian yang digunakan adalah metode deskriptif analisis. Kajian ini mendeskripsikan kualifikasi dan pengungkapan watak tokoh cerita sebagai pengantar dalam menafsirkan nilai moral yang terkandung di dalamnya. Cerita ini dipilih karena (1) belum pernah dikaji melalui  kajian sastra anak; (2) para tokoh penting diperankan oleh karakter binatang sehingga nilai fantasinya lebih tinggi daripada cerita dengan tokoh manusia; (3) cerita ini diperuntukkan bagi anak-anak terutama kelas 4, 5, dan 6; (4) memiliki cerita yang utuh; dan (5) merupakan cerita rakyat Maluku yang sudah dibukukan dan sudah berbahasa Indonesia bahkan sudah mengalami proses digitalisasi. Hasil kajian menunjukkan bahwa ada tujuh nilai moral yang disampaikan pengarang dalam tokoh cerita Buaya Learisa Kayeli, yaitu (1) janganlah takut membela kebenaran/menumpas kezaliman meskipun nyawa menjadi taruhannya supaya tercipta kehidupan yang harmonis dan tenteram; (2) hargailah orang yang telah berjasa dalam (menyelamatkan) hidupmu supaya terjalin persaudaraan yang abadi sampai akhir hayat; (3) janganlah suka mengganggu ketenangan hidup orang lain supaya tidak bernasib buruk di kemudian hari; (4) jangan pernah menyerah dalam berusaha supaya impianmu bisa tercapai; (5) berperangailah dengan baik terhadap orang lain supaya kamu bisa diterima oleh siapa pun dan di mana pun termasuk di lingkungan baru sekali pun; (6) bersabarlah dalam menghadapi rintangan kehidupan supaya buah dari kesabaran itu bisa bermanfaat bagi orang lain; dan (7) bersikap bijaklah terhadap lingkungan sekitar supaya tercipta keseimbangan alam yang sehat sehingga bisa memberikan keuntungan bagi umat manusia.